Community-based health coverage at the crossroad; the Muhammadiyah health fund in Indonesia - Agus Mohammad Samsudin; Harjanto Prabowo (Indonesian Journal of Islam and Muslim Societies, 2022)
This paper discusses the complexities of community-based health insurance (CBHI) coordinated by faith-based NGOs in Indonesia, and how government health care schemes threaten community-based health care plans. It discusses, in particular, Muhammadiyah’s history, one of the largest Islamic civil society organizations dealing with the health sector, as well as their struggle to facilitate community-based health care insurance. The role of state-based universal health coverage (UHC) has markedly overshadowed civil society programs, including faith-based NGOs, in implementing and providing health care services in their circles or members. While the State faces a delicate situation in the management of its universal health care, both financially and operationally, civil society groups have sought to revive the limited health care scheme as a way to supplement and even contend with the state welfare regime.